Continuous Ex-Offenders’ Reformation and Avoidance of Recidivistic Acts in Nigeria - Ayuk, A. Achu; Chimaobi, Okorie; Omang, T.A.; Nwankwo, E. Emeka (International Journal of Criminology and Sociology, 2022)
This paper arose from very serious concern emanating from the skyrocketed cases of recidivistic occurrences in Nigeria which as observed impact negatively on the Nigerian prison reformatory and rehabilitation processes vis-à-vis the security of lives and property. It is common now in Nigeria that our prison population keeps increasing without the corresponding facilities, manpower, and resources to effectively and efficiently reform inmates that after release would be better law-abiding and self-sustaining. From the study, it was revealed that ex-offenders become more hardened and daring, and prefer to habituate the prison environment to outside society. The lack and absence of training tools like mechanic workshops, tailoring shops, and more saddening the cruelty meted out on them inside the prison makes it worse; the stigmatization and outright denial of job opportunities as compared to their counterparts who are not ex-offenders are offensive to them. The study recommends as follows: Government should equip all correctional facilities in Nigeria with the approved international standards that through it inmates, after release, can be meaningfully engaged and be relatively self-sustaining; The government through its agencies like National Orientation Agency, federal radio, and television in conjunction with the religious bodies, sensitize the public on the danger of stigmatizing ex-convicts because it has far-reaching consequences; With the help of social workers, there should be follow-up and an evaluative scheme that requires an ex-offender constantly be monitored to prevent reoffending; and Schools should be established in the prisons and properly funded by the government to help to functionally educate and reshape the minds of the inmates so that upon release they will be better citizens.